Expression and diagnostic value evaluation of urinary exosomal miR-142-3p in diabetic nephropathy - Shengjie Li; Chuancai Sun; Shanshan Zheng; Sen Lin; Hao Li; Jing Wu; Yangyang Tian; Xinyuan Gao; Fang Qin; Yipeng Liu (Scientific Reports)
Abstract Diabetic nephropathy (DN) is one of the most severe microvascular complications of diabetes mellitus and a common cause of end-stage renal disease. Although kidney biopsy is the gold standard for diagnosing DN, it carries risks of complications such as infection and bleeding. Urinary microalbumin is currently used as a clinical indicator for diagnosing DN, but its early predictive ability is limited. Therefore, identifying non-invasive biomarkers for diagnosing DN has become a recent research focus. This study aimed to screen and identify differentially expressed miRNAs in diabetes and DN and evaluate their clinical diagnostic value to provide new directions for DN diagnosis. This study included 42 patients with diabetes and 57 patients with DN. Differentially expressed miRNAs in DN and type 2 diabetes mellitus were screened using the GEO database. General clinical data and urine samples were collected from both groups of patients. Urinary exosomes were extracted using ultracentrifugation, and qRT-PCR was used to detect changes in urinary exosomal miRNA expression between the two groups of patients. Receiver operating characteristic (ROC) curve analysis and Spearman correlation analysis were performed to evaluate the clinical diagnostic value of miRNAs. Urinary exosomal miR-142-3p was upregulated in DN patients compared to T2DM patients. ROC curve analysis showed that miR-142-3p had good diagnostic value for the disease and was positively correlated with UACR and risk stratification indicators for the progression of chronic kidney disease. Additionally, KEGG enrichment analysis revealed that urinary exosomal miR-142-3p may be involved in disease progression through pathways such as fatty acid metabolism, fatty acid biosynthesis, Hippo signaling pathway, cGMP-PKG signaling pathway, and Wnt signaling pathway. These results suggest that urinary exosomal miR-142-3p has good diagnostic performance in DN and may serve as a potential biomarker for diagnosing DN.